Fundamentals of probability and statistical evidence in criminal proceedings: guidance for judges, lawyers, forensic scientists and expert witnesses - Aitken, Colin; Roberts, Paul; Jackson, Graham (RSS, 2010)
An accessible introduction to the fundamentals of statistical evidence and probabilistic reasoning in criminal proceedings, providing guidance for judges, lawyers, forensic scientists and expert witnesses.